MANAJEMEN PEMBELAJARAN JARAK JAUH PADA PROGRAM SEKOLAH TERBUKA DI SMAN 04 BANDUNG DAN SMAS SEBELAS MARET BANDUNG - Lutviya Nilam Cahya (Jurnal Tata Kelola Pendidikan, 2021)
This study aims to provide an overview of the Distance Learning Management in the Open School Program at SMAN 04 Bandung and SMAS Sebelas Maret Bandung. Distance learning management in this open school program consists of lesson planning, learning implementation, learning evaluation, and learning supervision. This research is a descriptive study using a qualitative approach. The data collection technique in this study was through interviews, documentation studies, and observations which then used Nvivo software in data reduction. The results of this study indicate that distance learning management in open school programs includes 1) learning planning which is basically the same as regular school learning planning. However, there are differences in the open high school program system that is adapted to the place for learning and the provision of material time is only 1 hour/subject a week, 2) the implementation of learning that places more emphasis on online use and independent assignments, 3) learning evaluation which consists of task assessment , tests, and portfolios, and 4) supervision of learning carried out by the principal, assisted by the manager/person in charge of the open high school.